Incidence of Respiratory Syncytial Virus Lower Respiratory Tract Infections During the First 2 Years of Life: A Prospective Study Across Diverse Global Settings. (7th June 2022) - Langley, Joanne M; Bianco, Veronique; Domachowske, Joseph B; Madhi, Shabir A; Stoszek, Sonia K; Zaman, Khalequ; Bueso, Agustin; Ceballos, Ana; Cousin, Luis; D'Andrea, Ulises; Dieussaert, Ilse; Englund, Janet A; et al.
Abstract: Background: The true burden of lower respiratory tract infections (LRTIs) due to respiratory syncytial virus (RSV) remains unclear. This study aimed to provide more robust, multinational data on RSV-LRTI incidence and burden in the first 2 years of life. Methods: This prospective, observational cohort study was conducted in Argentina, Bangladesh, Canada, Finland, Honduras, South Africa, Thailand, and United States. Children were followed for 24 months from birth. Suspected LRTIs were detected via active (through regular contacts) and passive surveillance. RSV and other viruses were detected from nasopharyngeal swabs using PCR-based methods. Results: Of 2401 children, 206 (8.6%) had 227 episodes of RSV-LRTI. Incidence rates (IRs) of first episode of RSV-LRTI were 7.35 (95% confidence interval [CI], 5.88–9.08), 5.50 (95% CI, 4.21–7.07), and 2.87 (95% CI, 2.18–3.70) cases/100 person-years in children aged 0–5, 6–11, and 12–23 months. IRs for RSV-LRTI, severe RSV-LRTI, and RSV hospitalization tended to be higher among 0–5 month olds and in lower-income settings. RSV was detected for 40% of LRTIs in 0–2 month olds and for approximately 20% of LRTIs in older children. Other viruses were codetected in 29.2% of RSV-positive nasopharyngeal swabs. Conclusions: A substantial burden of RSV-LRTI was observed across diverse settings, impacting the youngest infants the most. Clinical Trials Registration. NCT01995175. Abstract : In a prospective, observational cohort study conducted in 8 countries across diverse settings, we found that RSV-LRTI burden is substantial during the first 2 years of life and tends to be higher among 0–5 month olds and in lower-income settings.